UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL KELAS V MELALUI METODE PERMAINAN DI SEKOLAH DASAR NEGERI 1 SUKARAME BANDAR LAMPUNG - Yusniar, Yusniar (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The objective of this research is to improve the students’ learning outcomes in the learning materials of social civic subject using game at the students in SD Negeri 1 Bandar Lampung. This study is classroom action research. The participants come from the students in SD Negeri 1 Bandar Lampung. From the data in the Social Sciences Learning about the diversity of tribes after improvements implemented by the method of the game, there is an increase in the study of students that is of 34.488% on prasiklus be 51.72% in the first cycle and increased to 86.21% in Cycle II. Thus it can be enriched by the method of learning games that can improve learning outcomes significantly in the Social Sciences Learning in Class V SD Negeri 1 Sukarame.